Effect of Endodontic Instrument Tip Fracture on Apical Sealing of Obturated Root Canal: In Vitro and Retrospective Clinical and Radiological Study (Journal of Hama University, 2019)
Endodontic treatment is affected differentially by fractured instrument, according to several variables such as separation locus in root canal. Secondary Procedural errors increase during fractured instrument retrieval attempts especially in apical region of root canal. This study aims to investigate effects of some variables contributing positively in organism support to retain of Apical Fractured Instrument (AFI). This study consists of retrospective clinical and radiological part distributed into 4 groups (n=10) with AFI: before or after root canal preparation then obturated by using modified single cone or thermal vertical condensing techniques. Clinical symptoms and radiological signs were followed up during 1 year, 3 year, 6 year. Variables of clinical part were mimicked by using in vitro groups (n=10) in order to observe stain microleakage into root canal apex, linked to apical sealing affected. Proper negative and positives controls were used. Statistical Analysis (P